WHAT DRIVES CAPITAL STRUCTURE? EVIDENCE FROM PROPERTY AND REAL ESTATE COMPANIES - Shasa Pramesti; Naelati Tubastuvi; Wida Purwidianti; Totok Haryanto (COMPETITIVE, 2025)
Capital structure is the ratio or composition of debt and equity used to finance a company's operational activities. Capital structure reflects long-term decisions related to funding sources and is an important factor in determining a company's risk and return. This study examines the influence of profitability, liquidity, company size, and asset structure on capital structure in the property and real estate sector listed in Indonesia. The population in this study consists of 94 companies in the property and real estate sector listed on the Indonesia Stock Exchange from 2021 to 2023. Data collection was conducted using the secondary method, employing purposive sampling and unbalanced data, resulting in a sample of 58 companies with 139 observations. The data were analyzed quantitatively using descriptive statistics. The results of this study indicate that profitability and asset structure do not influence capital structure. Liquidity has a negative impact on capital structure. Company size has a positive impact on capital structure. Based on the research findings, property and real estate companies should not rely on profitability and asset structure to determine their capital structure. Companies should focus on liquidity and company size, as higher liquidity reduces dependence on debt financing.